“Kept in Check”: Representations and Feelings of Social and Health Professionals Facing Intimate Partner Violence (IPV) - Di Napoli, Immacolata (Int J Environ Res Public Health, 2020)
Social and health professionals facing gender-based violence in Intimate Partner Violence (IPV) express feelings and thoughts closely connected to their place of work and the users of their services. However, research on professionals’ reflexivity and their implications has not been closely investigated. Therefore, this article will describe representations of IPV among social and health professionals facing gender-based violence as well as their personal feelings in accomplishing their job. Fifty interviews with health and social professionals were analyzed using grounded theory methodology supported by Atlas.ti 8.4. Five macrocategories will describe this phenomenon, leading to the final explicative core category that summarizes professionals’ attitudes toward it. Being “kept in check” among partners, partners and families, services, and institutional duties is the core category that best expressed their feelings. Therefore, implications for services and training will be further discussed.